Hubungan Dukungan Keluarga Dengan Kemandirian Lansia Dalam Melakukan PersonalHygiene Di Desa Gunungan Kecamatan Dawar BlandongKabupaten Mojokerto - Triwibowo, Heri; Frilasari & Yuli Rahmawati, Heni (JURNAL KEPERAWATAN BINA SEHAT, 2017)
AbstrakThe process of aging is a natural process, can not be prevented and is a natural thing. The aging process still causes problems both physical, mental and social economy, so age is expected to elderly still get the quality of lite remains good, independent and maintain their health. Objective Research to determine the relationship of family support to theindependence of elderly people in doing personal hygiene in the village of Dawar blandong Gunungan District of Mojokerto,In this study design used is analytic corelational, Corelational analytical research population is all the families who have elderly people aged 60-74 years in the village of Dawar blandong Gunungan District of Mojokerto number of432 people with a sample with a sample of 43 people sampling techniques using random cluster sampling, the independent variable in this study is the family support and dependenya is the independence of the elderly. Data were analyzed using chi-square test, Research results are mostly families supporting elderly people independence in conducting personal higycnc as many as 24 respondents (55.8%) and the majority had mild dependence as much as 13respondents (30.2%). The results of chi square test at the significant level a= 0.05 was found that p <a or 0.000 <0.05 HO rejected HI accepted which means no family support relationships with elderly people independence in performing personal hygiene in the village of Dawar blandong Gunungan District of Mojokcrto .Tcnaga health considerations should have to provide input in improving the welfare of the elderly through education in families with elderly.Keywords : family support, self-reliance, the elderly , personal hygiene